Προσεγγίσεις σε κείμενα νεότερης και σύγχρονης ποίησης - Τοπούζης, Κώστας, 1927-2011 (Gutenberg, 1984)
Σικελιανός Βάρναλης Καρυωτάκης Καβάφης Σεφέρης Παπατσώνης Ρίτσος Ελύτης Βρεττάκος Παππάς Κρανιδιώτης Παυλέας Θέμελης Βαρβιτσιώτης Δικταίος Καρούζος Σαχτούρης Σινόπουλος Αναγνωστάκης